Prophetic Leadership and Competitive Advantage: The Role of Total Quality Management - Bidayati, Utik; Azzahra, Tania Chusna (Jurnal Manajemen Bisnis, 2026)
Research aims: This study examines the effect of prophetic leadership on university lecturers’ competitive advantage, with total quality management (TQM) serving as a mediating variable.Design/Methodology/Approach: A quantitative approach was employed using data from 264 university lecturers in Indonesia, selected through purposive sampling. Data were collected via a questionnaire and analyzed using SmartPLS 4.0.Research findings: The results indicate that prophetic leadership positively affects TQM but has a negative direct effect on competitive advantage. In contrast, TQM positively influences competitive advantage. Moreover, TQM acts as a mediating mechanism through which the positive effect of prophetic leadership is translated into competitive advantage.Theoretical Contribution/Originality: This study contributes theoretically by integrating prophetic leadership, grounded in Islamic ethical and spiritual values, into the leadership discourse in higher education, an area that remains underexplored in mainstream academic literature.Practitioners/Policy Implications: Theoretically, this study extends the higher education leadership literature by incorporating religious and ethical values. Practically, university management can develop prophetic leadership programs and implement TQM systems to enhance the quality and long-term competitiveness of academic staff.Research Limitations/Implications: First, the sample is confined to specific geographic areas in Indonesia, which may limit the generalizability of the findings. Second, the quantitative approach does not fully capture the perceptions and contextual dynamics involved in implementing prophetic leadership and TQM in practice.